Evaluasi Peraturan Walikota Bengkulu Nomor 37 Tahun 2021 Tentang Pelaksanaan Peraturan Daerah Kota Bengkulu Nomor 02 Tahun 2017 Tentang Penyelenggaraan Penanggulangan Bencana (Studi di Daerah Rawan Banjir Kota Bengkulu) - Tesa Dwi Suryana; Bobi Mandala Putra; Henny Aprianty (Journal of Innovative and Creativity, 2025)
Flooding is a recurring natural disaster in Bengkulu City, occurring two to three times a year. The Regional Disaster Management Agency (BPBD) of Bengkulu City has identified three flood-prone districts: Muara Bangkahulu, Sungai Serut, and Ratu Agung. The purpose of this study is to evaluate the implementation of post-flood rehabilitation policies as regulated in Article 9 of the Mayor Regulation of Bengkulu Number 37 of 2021 concerning the Implementation of Bengkulu City Regional Regulation Number 02 of 2017. The evaluation focuses on environmental restoration, public infrastructure improvement, housing repairs, and health services. This study employs a descriptive qualitative approach with data analysis techniques that include data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of the rehabilitation policy has not been optimal. There is weak coordination between BPBD and related agencies, limited community participation in maintaining environmental sustainability, and constraints in terms of human resources and available budget. These shortcomings have hindered the achievement of the policy’s intended outcomes.In conclusion, this study highlights the need for stronger inter-agency collaboration, better resource allocation, and more active community involvement to support effective post-flood rehabilitation in Bengkulu City. Improving these aspects will enhance the city's resilience and preparedness for future flooding events.